Cyclin A1 expression predicts progression in pT1 urothelial carcinoma of bladder: a tissue microarray study of 149 patients treated by transurethral resection. Issue 2 (7th January 2015) - Munari, Enrico; Chaux, Alcides; Maldonado, Leonel; Compérat, Eva; Varinot, Justine; Bivalacqua, Trinity J; Hoque, Mohammad O; Netto, George J
<x xml:space="preserve">Abstract</x> Aims To evaluate the immunoexpression of cyclin A1 in pT1 urothelial carcinomas of the bladder (UC) from a cohort of patients treated by transurethral resection of the bladder (TURB), to determine its value in predicting tumour recurrence, tumour progression, or systemic metastases. Methods and results Five tissue microarrays (TMAS) were constructed from representative paraffin blocks of high‐grade pT1 UC from 149 consecutive patients. Cyclin A1 immunoexpression was evaluated as the percentage of tumour cells with positive nuclear staining estimated at each TMA spot. The cutoff for cyclin A1 positivity was set at 10% of cells. Outcome variables included tumour recurrence and tumour progression as the primary endpoints. Cyclin A1 positivity was associated with tumour progression but not with tumour recurrence or the presence of adjacent carcinoma in situ in the biopsy. Also, patients with pT1b at biopsy and cyclin A1 expression showed higher progression rates than patients with pT1a at biopsy and without cyclin A1 expression, respectively. Combining pT1 stage at biopsy and cyclin A1 expression more accurately predicted tumour progression than pT1 stage at biopsy alone and cyclin A1 expression alone. Conclusions Cyclin A1 immunoexpression is of potential utility in predicting disease progression in patients with pT1 UC.